2007
DOI: 10.1016/s1808-8694(15)30106-3
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Epley’s maneuver in the same session in benign positional paroxysmal vertigo

Abstract: Repeated Epley's maneuvers in less sessions rendered more positional nystagmus-free patients when compared to those submitted to more sessions of single maneuvers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 36 publications
1
49
0
5
Order By: Relevance
“…This procedure was based on the observations that repeated Epley manoeuvres in fewer sessions render more positional nystagmus-free patients when compared to those submitted to more sessions of single maneuvers [21]. However, we showed that multiple maneuvers did not enhance efficacy as measured by VAS scores and even increased the perceived dizziness during the 5 days following the therapeutic maneuver.…”
Section: Discussionmentioning
confidence: 85%
“…This procedure was based on the observations that repeated Epley manoeuvres in fewer sessions render more positional nystagmus-free patients when compared to those submitted to more sessions of single maneuvers [21]. However, we showed that multiple maneuvers did not enhance efficacy as measured by VAS scores and even increased the perceived dizziness during the 5 days following the therapeutic maneuver.…”
Section: Discussionmentioning
confidence: 85%
“…Epley manevar predstavlja repozicionu proceduru koja ima za cilj da serijom od pet uzastopnih pokreta glave i tela, koji se izvode pod kontrolom lekara, oslobodi zadnji polukružni kanal od slobodno plutaju eg otokonijalnog debrisa i pošalje ga nazad u utrikulus.Visok procenat izle ivosti BPPV-a zadnjeg polukružnog kanala objavio je ve i broj Objavljen je i manji broj studija koje su upore ivale razliku izme u efikasnosti izvo enja samo jednog manevra Epleye u odnosu na ponavljano izvo enje, u jednom tretmanu dok tegobe ne prestanu (do etiri menevra) 1,15 . Ve a efikasnost ponavljanja manevara u jednom tretmanu još uvek je pitanje kotroverzi.…”
Section: Diskusijaunclassified
“…Korn i sar. 15 navode da se postiže za 21,4% ve a efikasnost izvo enjem etiri manevra Epley u jednom tretmanu u odnosu na izvo enje samo jednog manevra. S obzirom na to da kod BPPV-a spontana remisija tegoba nije retka pojava, efikasnost pojedinih terapijskih procedura može biti i precenjena.…”
Section: Diskusijaunclassified
“…Outros autores descreveram também os benefícios proporcionados pela manobra de Epley, no qual pela avaliação de dois grupos de pacientes, perfazendo um total 123 pessoas, identificaram a redução significativa do aparecimento de episódios de nistagmo no grupo tratado com a intervenção da manobra em quatro momentos numa mesma terapia, em relação ao grupo que a realizou uma única vez por sessão durante algumas semanas, considerando que apenas o procedimento de tratamento com esta manobra de reposicionamento pode ser benéfico para a redução dos sinais e sintomas clínicos da VPPB 16 . Os resultados demonstraram que a realização apenas da manobra pode ser suficiente para o tratamento das pessoas com VPPB, sem necessitar de variações e associações de outras terapias para atingir um bom resultado terapêutico como visto em outros trabalhos na mesma área.…”
Section: Discussionunclassified